2013
DOI: 10.3928/23258160-20130909-09
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhagic Age-Related Macular Degeneration Managed With Vitrectomy, Subretinal Injection of Tissue Plasminogen Activator, Gas Tamponade, and Upright Positioning

Abstract: In patients with hemorrhagic neovascular AMD, treatment with vitrectomy, subretinal tPA injection, gas tamponade, and upright positioning was associated with better visual outcomes than those reported for patients with untreated disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 38 publications
0
14
1
Order By: Relevance
“…Neovascular age-related macular degeneration (nAMD) is a major cause of vision loss among the elderly population in Western countries [ 1 2 ]. Before the era of anti-vascular endothelial growth factor treatment, visual loss prevention was only achieved in a limited number of patients despite the use of different treatment modalities [ 3 4 5 6 7 ]. Bevacizumab, ranibizumab, and finally aflibercept treatments have led to conservation of baseline visual acuity (VA) in the vast majority of patients and significantly increased VA in approximately one-third of patients [ 8 9 10 11 12 ].…”
mentioning
confidence: 99%
“…Neovascular age-related macular degeneration (nAMD) is a major cause of vision loss among the elderly population in Western countries [ 1 2 ]. Before the era of anti-vascular endothelial growth factor treatment, visual loss prevention was only achieved in a limited number of patients despite the use of different treatment modalities [ 3 4 5 6 7 ]. Bevacizumab, ranibizumab, and finally aflibercept treatments have led to conservation of baseline visual acuity (VA) in the vast majority of patients and significantly increased VA in approximately one-third of patients [ 8 9 10 11 12 ].…”
mentioning
confidence: 99%
“…To date, various surgical techniques and pneumatic methods have been investigated for manipulating the SMH and displacing it [4], [5], [6], [7], [8], [9], [10], [11], [12], [13], [14], [15]. Techniques consisting of vitrectomy and direct subretinal removal of the SMH have been found ineffective.…”
Section: Discussionmentioning
confidence: 99%
“…In patients diagnosed with nAMD limited to one eye, neovascular lesions associated by any amount of hemorrhage were found to develop in the other eye in 19% during 4 years of follow up 6 . As visual outcomes of SMH are usually devastating, several treatment options have been evaluated for its treatment including intravitreal injection of gases and tissue plasminogen activator (tPA), vitrectomy with or without intravitreal/subretinal tPA injection and pneumatic displacement of the hemorrhage [4], [5], [6], [7], [8], [9], [10], [11], [12], [13], [14], [15]. A consensus on the best approach to therapy has not yet emerged 8 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Before the era of intravitreal anti-vascular endothelial growth factor (anti-VEGF) agents, only prevention of visual loss might have been achieved in a limited number of patients despite the use of different treatment modalities. [3][4][5][6][7][8] Bevacizumab, ranibizumab, and finally aflibercept have led to the conservation of the baseline visual acuity (VA) in the vast majority of the patients and have given the chance of increasing VA significantly in approximately one third of the patients. [9][10][11][12] Multicenter studies have shown that ranibizumab is effective in the prevention of VA loss in up to 95% of the patients, and an improvement in VA can be achieved in up to 40% of the patients.…”
Section: Introductionmentioning
confidence: 99%